Attitudes and related factors toward organ donation among relatives of chronic kidney disease patients and healthy individuals - Yakar, Burkay; Batbas, Canan Sertdemir; Onalan, Erhan; Icacan, Gamze; Demir, Mustafa (Cukurova Univ, Fac Medicine, 2020)
Purpose: The current study firstly aimed at investigating organ donation and related factors. Another aim of the study is to compare the knowledge and attitude levels of organ donation between the risky population with organ failure and healthy participants. Materials and Methods: This cross-sectional survey was conducted in the tertiary university hospital between March-October 2019. A total of 88 healthy participants (group 1) and 56 participants with chronic kidney disease ((CKD) (group 2)) were included in the study. Organ donation attitudes of participants were measured with Organ Donation Attitudes Scales Turkish Version questionnaire. Result: A total of 144 participants (56 were CKD patients and 88 healthy participants) were included in the study. The scores of all participants from the sub-dimensions of the scale were humanity and moral conviction / beliefs (HMC): 90.7020.36, fears of medical neglect (FMN): 27.38 +/- 11.52 and fears of bodily mutilation (FBM): 32.03 +/- 10.67, respectively. Group 2 participants' humanity and moral conviction/beliefs (HMC) dimension scores were higher than group 1. Group 2 participants' fears of medical neglect (FMN) score was higher than group 1. Factors affecting organ donation attitudes were gender and education level. Conclusion: Organ donation positive attitude scores were higher in women and those with higher education levels. Our results may suggest developing empathy and education programs on organ transplantation, as a means for increasing the number of potential organ donors.
Keywords: Organ donation; attitude; tissue and organ procurement; organ transplantation; empathy